Novel Method for the Synthesis of α-Amino-α′-hydroxyalkylphosphinic Acids and Bis(α-aminoalkyl)phosphinic Acids: Nuclephilic Addition of α-Hydroxy-H-phosphinic Acids to Diimines - Kaboudin, Babak; Haghighat, Hamideh; Alaie, Saied; Yokomatsu, Tsutomu (Synlett, 2012)
We report here a novel and simple method for the synthesis of α-amino-α′-hydroxyalkylphosphinic acids in good yields in two simple steps without any protection–deprotection steps. We have developed an efficient method for the synthesis of α-amino-α′-hydroxyalkylphosphinic acids via the reaction of easily available α-hydroxyalkylphosphinic acids with diimines. Treatment of α-hydroxyalkylphosphinic acids with diimines in the presence of trimethylsilyl chloride (TMSCl) gives α-amino-α′-hydroxyalkylphosphinic acids in good yields. The reaction gave a mixture of two diastereomeric forms of α-amino-α′-hydroxyalkylphosphinic acids. The difference in solubility in organic solvents allowed us to readily separate the diastereoisomers.
Keywords: phosphinic acids; hydroxyalkylphosphinic acid; amino-α′-hydroxyalkylphosphinic acid; diimines; bis(α-aminoalkyl)phosphinic acid